2017
DOI: 10.3389/fphar.2017.00595
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of HLA Class I Expression on Tumor Cells by the Anti-EGFR Antibody Nimotuzumab

Abstract: Defining how epidermal growth factor receptor (EGFR)-targeting therapies influence the immune response is essential to increase their clinical efficacy. A growing emphasis is being placed on immune regulator genes that govern tumor -T cell interactions. Previous studies showed an increase in HLA class I cell surface expression in tumor cell lines treated with anti-EGFR agents. In particular, earlier studies of the anti-EGFR blocking antibody cetuximab, have suggested that increased tumor expression of HLA clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…14,15 In addition, EGFR-TKIs can potentiate the induction of MHC class I and II molecules in response to IFN-γ and enhance T cell-mediated tumor killing. 16,17 These studies support the potential synergistic effects of combining PD-1/PD-L1 inhibitors and EGFR targeted therapy in NSCLC patients. Although many clinical trials have attempted to explore this combination in NSCLC cases, the results have shown that the clinical benefits are far below expectations.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…14,15 In addition, EGFR-TKIs can potentiate the induction of MHC class I and II molecules in response to IFN-γ and enhance T cell-mediated tumor killing. 16,17 These studies support the potential synergistic effects of combining PD-1/PD-L1 inhibitors and EGFR targeted therapy in NSCLC patients. Although many clinical trials have attempted to explore this combination in NSCLC cases, the results have shown that the clinical benefits are far below expectations.…”
Section: Introductionmentioning
confidence: 56%
“…Preclinical results have shown that EGFR activation can upregulate intrinsic PD‐L1 expression on tumor cells, which induces T‐cell apoptosis and contributes to the immune escape of EGFR ‐mutant NSCLC . In addition, EGFR‐TKIs can potentiate the induction of MHC class I and II molecules in response to IFN‐γ and enhance T cell‐mediated tumor killing . These studies support the potential synergistic effects of combining PD‐1/PD‐L1 inhibitors and EGFR targeted therapy in NSCLC patients.…”
Section: Introductionmentioning
confidence: 57%
“…As deactivation of IFNGR1 did not lead to the downregulation of the PD-L1 and MHC-I molecules on TC-1/dIfngr1 and TC-1/A9/dIfngr1 cells in vivo compared to TC-1 and TC-1/A9 cells, respectively, we hypothesized that besides IFN-γ, other cytokines induced PD-L1 and MHC-I expression. Several studies have indicated the involvement of different factors (IFN-α, IFN-β, IL-27, EGF, TNF-α, IL-6, GM-CSF, IL-1α, and CCL2 combined with lipocalin 2) in PD-L1 and MHC-I stimulation or stabilization [27,[29][30][31][32][33][34][35][36][37][38][39]. In this study, type I IFNs (IFN-α and IFN-β) were the main inducers of PD-L1 and MHC-I expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that expression of MHCI and/or MHCII molecules can impact the antitumor immune response [103][104][105]. IFN-γ potentiates the induction of MHC class I (MHCI) and II (MHCII) molecules [102,106]. Watanabe et al found that EGFR-mutant cells have lower levels of human leukocyte antigen (HLA)-B expression than do EGFR-wildtype cells [107] in the presence of IFN-γ.…”
Section: Cell Surface Molecules and Selected Soluble Factorsmentioning
confidence: 99%